Traceability and risks: an extended transaction cost perspective. Issue 2 (13th March 2017) - Stranieri, Stefanella; Orsi, Luigi; Banterle, Alessandro
Abstract : Purpose: The aim of the paper is to investigate the determinants leading firms to choose among different voluntary standards within food supply chains. In specific, the authors explored the role of transaction risks, i.e. internal and exogenous risks, in the adoption of different traceability standards. Design/methodology/approach: A survey was conducted within the Italian population of 216 food-processing firms that adopt voluntary traceability schemes. The identification of different transaction risks was based on the literature on supply chain management and transaction cost economics. An ordinal regression model was used in the analysis. Findings: Empirical results highlight that the transaction risks perceived by food firms play a significant role on the kind of traceability schemes to adopt. There is a positive link between internal risks and the decision to implement complex schemes. Moreover, a negative relationship between the perceived exogenous risks and the complexity of the standard adopted is also observed. Exogenous transaction risk lead to the implementation of standards which do not imply strong co-ordination. On the contrary, internal risks imply complex schemes that lead to closer supply chain relationships. Research limitations/implications: The analysis is limited to cross-sectional data for a single country, and further investigation would help assess the generalisation of the findings. Practical implications: The analysis can be considered a useful framework to orient firms strategic decisions towards the most appropriate voluntary standard to adopt for an efficient management of vertical relationships within food supply chains. Originality/value: The present analysis is the first attempt to explain the determinants leading firms to choose among different kinds of voluntary standards within food supply chains. The approach used reveals that transaction risks can be considered a useful framework to explain firms' strategic decisions related to the kind of schemes to adopt.